Dampak Kualitas Produk, Harga dan Word Of Mouth terhadap Minat Beli pada Butik Islamiyah Taqwa Travel Palembang - Aidil Fitriansyah; Nuraida Nuraida; Emi Puspita Dewi (Social Science and Contemporary Issues Journal, 2024)
The impact on income is due to efforts to improve product quality and price again so as to create a good image for the company, so the researchers determined the title "The Impact of Product Quality, Price and Word of Mouth on Purchase Interest at the Islamiyah Taqwa Travel Palembang Boutique." The aim of the research is to determine the impact of product quality, price and word of mouth on purchasing interest at the Islamiyah Taqwa Travel Palembang boutique. The type of research is quantitative statistics. Data collection techniques include observation, questionnaires and documentation. Then the data analysis technique uses validity, reliability, homogeneity, normality, heteroscedasticity, multicollinearity, multiple linearity and hypothesis tests. The results of the research show that the Fcount value is 55.410>2.69 Ftable, the significant value is 0.000 <0.05, so there is a simultaneous influence between the variables of product quality, price, Word of Mouth on purchase intention received. This means that the influence of the product quality variable (X1), price variable (X2), Word of Mouth (X3) and purchase interest variable (Y) is 84.9%, meaning that there is a significant impact between product quality, price, word of mouth regarding buying interest is due to strong internal encouragement or stimulation to motivate action, where this encouragement is influenced by stimulus and positive feelings about the products that consumers want to have from Butik Islamiyah Taqwa Travel Palembang